2021
DOI: 10.1002/prp2.902
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Jujube syrup on the prevention of drug‐induced hepatotoxicity in pulmonary tuberculosis patients: A pilot randomized double‐blind placebo‐controlled clinical trial

Abstract: Liver injury is the most common complication of anti‐tuberculosis drugs that can cause significant problems. The study aimed to determine the effectiveness of Jujube syrup on the prevention of antituberculosis drug‐induced hepatotoxicity (DIH). This pilot randomized double‐blind study was conducted based on a placebo‐controlled design in patients with tuberculosis (TB). The patients were divided into two groups based on the block random allocation method and received 10 cc of jujube or placebo syrup per day. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Jujube is traditionally considered a tonic for enhancing liver function and preventing hepatic diseases. As shown in Table 6, in a clinical study on tuberculosis patients, jujube syrup effectively prevented antituberculosis drug-induced liver damage [58]. According to animal and cellular experiments, jujube polysaccharide and flavonoid improved liver impairment by activating the body's antioxidant system and inhibiting inflammatory responses [8,12].…”
Section: Hepatoprotectionmentioning
confidence: 98%
“…Jujube is traditionally considered a tonic for enhancing liver function and preventing hepatic diseases. As shown in Table 6, in a clinical study on tuberculosis patients, jujube syrup effectively prevented antituberculosis drug-induced liver damage [58]. According to animal and cellular experiments, jujube polysaccharide and flavonoid improved liver impairment by activating the body's antioxidant system and inhibiting inflammatory responses [8,12].…”
Section: Hepatoprotectionmentioning
confidence: 98%
“…The results revealed a remarkable finding, as 27.3% of the placebo group exhibited hepatotoxicity, while no toxicity was observed in the jujube group. Additionally, the treatment group showed a significant improvement in the quality of life compared to the placebo group (Maddahi et al, 2022). In another double‐blind, randomized, placebo‐controlled trial (NCT01800487), the clinical effectiveness of silymarin against antituberculosis DILI was tested.…”
Section: Natural Products Against Dili: From Bench To Bedside?mentioning
confidence: 99%
“…Epidemiological studies indicated that body mass index (BMI) was negatively associated with the risk of TBLI (7). Randomized controlled trials indicated that carnitine, jujube syrup, and Lactobacillus casei could provide protection against TBLI (8)(9)(10). Carnitine and jujube syrup alleviated hepatocellular damage-type TBLI, which manifested as significant elevations of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled trials indicated that carnitine, jujube syrup, and Lactobacillus casei could provide protection against TBLI (8)(9)(10). Carnitine and jujube syrup alleviated hepatocellular damage-type TBLI, which manifested as significant elevations of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) (8,9). The L. casei intervention alleviated cholestasis-type TBLI (manifested as significant elevations of alkaline phosphatase and total bilirubin) by modulating the gut microbiota, reducing the blood liposaccharide content, and improving intestinal permeability (10).…”
Section: Introductionmentioning
confidence: 99%